2010
DOI: 10.1111/j.1365-2818.2010.03408.x
|View full text |Cite
|
Sign up to set email alerts
|

Region-of-interest tomography using filtered backprojection: assessing the practical limits

Abstract: SummaryThere are many cases where it is desirable to reconstruct at high resolution a small volume from a larger sample. Here we describe the outcomes of a reconstruction trial based on real samples aimed at delineating the practical limits to which a small region of interest can be viewed from a large sample. Our approach has been to artificially truncate the sinograms of whole sample scans to simulate region of interest tomography. A simple filtered back projection algorithm has been applied, with the sinogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 43 publications
2
82
0
1
Order By: Relevance
“…For many applications, constant extrapolation provides acceptable results (Kyrieleis et al, 2011), although cupping artifact makes the segmentation challenging.…”
Section: Sinogram Extrapolation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many applications, constant extrapolation provides acceptable results (Kyrieleis et al, 2011), although cupping artifact makes the segmentation challenging.…”
Section: Sinogram Extrapolation Methodsmentioning
confidence: 99%
“…The Filtered Backprojection (FBP) with sinogram extrapolation is widely used in local tomography because it is both simple and gives satisfactory results in general (Kyrieleis et al, 2011). Theoretical investigations found that FBP provides a reconstructed function bearing the same discontinuities as the reference function (Bilgot et al, 2009) , although the cupping effect can make the segmentation challenging.…”
Section: Correcting the Reconstruction Error In The Imagementioning
confidence: 99%
“…A drawback with this method is that it requires very accurate registration of the two sets of radiographs (Kyrieleis et al 2011).…”
Section: Future Challenges and Opportunitiesmentioning
confidence: 99%
“…2). If this padding is carried out by extending the pixel values at the outer edges of each sinogram, and the number of projections is based not on the ROI diameter, but the diameter of the entire sample, the suppression of artifacts can be highly satisfactory (Kyrieleis et al 2011).…”
Section: Future Challenges and Opportunitiesmentioning
confidence: 99%
“…To avoid severe imaging artefacts, this volume should have similar size as the complete sample (Kyrieleis et al, 2011). For technological and computational reasons, is usually limited to several thousands of pixels, which sets a limit to the achievable voxel size as a function of the sample size.…”
Section: Discretization Effectsmentioning
confidence: 99%